(untitled) (Journal of Environmental Science and Natural Resources, 2015)
The study was conducted in January to March 2012 of two villages of Alamdanga upazila under Chuadanga district to observe the knowledge of farmers about using the chemical fertilizers and organic manure and also to determine the awar eness of the farmers towards the use of the chemical fertilizers and the use of organic manure. In order to conduct this research, a questionnaire survey was carried out and interview was taken total 100 farmers. This paper describes some findings that around 19% of the farmers had highly favorable attitude while 66% had moderately favorable attitude and 15% had slightly favorable attitude towards the use of chemical fertilizers and organic manure. Moreover by this research it is suggested that the education and annual income can change the attitude of farmers in the field of crop cultivation. DOI: http://dx.doi.org/10.3329/jesnr.v7i2.22207 J. Environ. Sci. & Natural Resources, 7(2): 69-72 2014